AN ANALYSIS OF THE SOCIAL AND ECONOMIC SUPPORT SERVICES OF THE MINISTRY OF FAMILY AND SOCIAL POLICIES IN TURKEY - Cemre BOLGÜN; Edip AYGÜLER; Mustafa Çağrı AYALP (International Journal of Eurasia Social Sciences, 2018)
One of the social policy implementations in Turkey affected by the globalization process and neo-liberal politics is Social and Economic Support (SED) services. It is provided by the General Directorate of Child Services of the Ministry of Family and Social Policy. SED services are provided for children who do not need institutional care as long as they are supported. SED services are directly linked to the poverty-based child protection services. The main objective of this study is to address the SED services, one of the social policy implementations for the prevention of child poverty, to present the current situation and deficiencies. In this study, data related to SED services will be discussed in terms of neo-liberal policies and conservative theory. In addition; the number of aid recipients within years and their share in GDP will be discussed. In conclusion, in addition to significant positive contributions, SED services appear to have significant shortcomings. In particular, the non-systematic and non-comprehensive implementations of follow-up and monitoring processes, lack of social and psychological support services are outstanding problems. These aspects are of great importance in terms of providing relief from the welfare dependency of the service. Moreover, with the influence of neo-liberalism and conservative approaches, social welfare responsibilities of the state are transferred to other institutions (traditional charitable organizations, NGOs, voluntary organizations, etc.) to a certain extent. In addition, it is believed that the current practice centralizes the family while not considering the women’s burden of care.